Draft Genome Sequence of ‘Candidatus Phytoplasma pyri’ Strain P1, the Causal Agent of Pear Decline Disease - Alessio, Florencia Ivette; Bongiorno, Vanina Aylén; von Backzo, Oscar Hernan; Marcone, Carmine; Conci, Luis Rogelio; Fernandez, Franco Daniel (The American Phytopathological Society, 2026)
This study reports the draft genome of ‘Candidatus Phytoplasma pyri’ strain P1, isolated from Argentina. The genome assembly consisted of 17 contigs, with a total length of 575,431 bp, a GC content of 20.35%, and 125× coverage. A total of 537 genes were annotated, including those related to metabolism, genetic information processing, and signaling. Phylogenetic analysis placed ‘Ca. Phytoplasma pyri’ within the 16SrX group, supporting its classification as a distinct species from ‘Ca. Phytoplasma mali’ and ‘Ca. Phytoplasma prunorum’, with average nucleotide identity values ranging from 90.3 to 90.5%. In contrast, strain P1 shares 98.1% average nucleotide identity with the Chilean strain ‘Ca. Phytoplasma pyri’ UCh_1, supporting their classification as members of the same species. The investigation also identified 12 secreted proteins, including homologs of known effectors, as well as conserved proteins associated with virulence mechanisms. A homolog of the immunodominant membrane protein was also characterized, revealing conserved gene organization across related strains. These findings contribute to the understanding of ‘Ca. Phytoplasma pyri’ pathogenicity and provide valuable genomic data for future research.